ANALISIS PENGENDALIAN KUALITAS PROSES PRODUKSI SOL SANDAL PADA PT. CIPTA PRIMA - Charles Wiryahadi Kusuma; Carla Olyvia Doaly (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
In the production process, the company must maintain the quality of the products produced. Maintained quality will increase the company's competitiveness. PT. Cipta Prima maintains product quality by conducting quality inspections of each product produced. In the period from September 20, 2021 to October 25, 2021, PT Cipta Prima produced a total of 265,104 pieces of sandal soles and shoes made of rubber. Rubber is a good material for soles of sandals and shoes. There are 2 defects, namely, Excessive Paint and Damaged Rubber with a total of 27,133 defects. To reduce these defects, it is necessary to analyze the production process. The analysis is carried out using tools in the form of P Control Map, Pareto Diagram, Fishbone Diagram and Why – why Analysis. Based on the results of the analysis that has been carried out, one of the influencing factors is workers who are less trained and lack of machine maintenance. The solution needed for this problem is to increase the standard of hiring workers at PT. Cipta Prima, provides training for workers on a regular basis to comply with SOPs and machine maintenance is carried out regularly so that it is always optimal and standardizes the order of the production line and ensures that all workers carry it out according to standards and then improves the lighting section on the production floor. It is hoped that the solutions provided can improve the quality of products from PT. Prima Cipta.